Early insulin initiation in type 2 diabetes: efficacy, safety, and clinical implications: a systematic review with narrative synthesis - Osama Albasheer; Amal H. Mohamed; Nagla Abdalghani; Areej Hamdi; Doaa Abdulwahab Mohammed Ayish; Fatma Ayish; Ayyub Alssum; Ali Yahya Maashi; Lamyaa A. M. El Hassan; Tahani Madkhali; Mohammed Muqri; Aisha A. Awaf; et al. (Frontiers in Endocrinology, 2026)
Aims/background Early insulin initiation in type 2 diabetes mellitus (T2DM) is proposed to improve glycemic control, preserve β-cell function, and potentially reduce long-term complications. Evidence suggests that starting insulin within five years of diagnosis may offer additional metabolic benefits, but its clinical impact remains uncertain. This systematic review aimed to evaluate the efficacy, safety, and challenges of early insulin use in T2DM. Methods We systematically searched PubMed, Cochrane Library, Scopus, and Controlled Trials Register for studies published from 2010 to 2024, including adults with T2DM who initiated insulin within five years of diagnosis. Sixteen studies met inclusion criteria (9 RCTs, 7 observational), totaling 44, 045 participants. Two reviewers independently extracted data on glycemic outcomes, adverse events, and long-term complications. Risk of bias was assessed using the Cochrane tool for RCTs and the JBI checklist for observational studies. Due to substantial clinical and methodological heterogeneity, a meta-analysis was not performed, and findings were synthesized narratively. Results Early insulin therapy significantly reduced HbA1c (by 0.8–2.3%, p<0.05) and fasting glucose (by 1.2–2.4 mmol/L). Hypoglycemia occurred in 8–15% of insulin users compared to 3–10% with oral agents; severe episodes were rare (<2%). Weight gain over 2 kg was reported in nearly half of the studies. Conclusion Early insulin initiation improves glycemic outcomes and may preserve β-cell function. However, increased risks of hypoglycemia and weight gain warrant individualized treatment decisions. Future studies should adopt standardized definitions and assess long-term cardiovascular outcomes. Systematic review registration https://www.crd.york.ac.uk/prospero/ , identifier CRD42024508356.